Excel crashed while computing this

Algebra Level 4

x 4 + 3 x 3 + 4 x 2 + 3 x + 1 = 0 x^4+3x^3+4x^2+3x+1=0

Let a , b , c , a,b,c, and d d be the not necessarily distinct roots of the equation above. Find the value of the expression below:

a 1024 + b 1024 + c 1024 + d 1024 + 1 a 1024 + 1 b 1024 + 1 c 1024 + 1 d 1024 . a^{1024}+b^{1024}+c^{1024}+d^{1024}+\frac{1}{a^{1024}}+\frac{1}{b^{1024}}+\frac{1}{c^{1024}}+\frac{1}{d^{1024}}.


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

8 solutions

Using the Rational Root Theorem, we find that 1 -1 is a root. Since x 4 + 3 x 3 + 4 x 2 + 3 x + 1 x^4+3x^3+4x^2+3x+1 is a reciprocal equation, we find that 1 1 = 1 \dfrac{1}{-1}=-1 is another root, meaning that 1 -1 is a double root. Then, dividing by x 2 + 2 x + 1 x^2+2x+1 gives x 2 + x + 1 x^2+x+1 . Hence, x 4 + 3 x 3 + 4 x 2 + 3 x + 1 = ( x + 1 ) 2 ( x 2 + x + 1 ) x^4+3x^3+4x^2+3x+1=(x+1)^2(x^2+x+1) Hence a = b = 1 , c = ω , d = ω 2 a=b=1, c=\omega, d=\omega^2 where ω \omega and ω 2 \omega^2 are the non-real cube roots of unity. Hence: a 1024 + b 1024 + c 1024 + d 1024 + 1 a 1024 + 1 b 1024 + 1 c 1024 + 1 d 1024 = 1 + 1 + ω 1023 × ω + ( ω 2 ) 1023 × ω 2 + 1 + 1 + 1 ω 1023 × ω + 1 ( ω 2 ) 1023 × ω 2 = 4 + 2 ω + 2 ω 2 = 2 ( 1 + ( 1 + ω + ω 2 ) ) = 2 × 1 = 2 a^{1024}+b^{1024}+c^{1024}+d^{1024}+\frac{1}{a^{1024}}+\frac{1}{b^{1024}}+\frac{1}{c^{1024}}+\frac{1}{d^{1024}}\\=1+1+\omega^{1023}\times \omega+(\omega^2)^{1023}\times \omega^2+1+1+\frac{1}{\omega^{1023}\times \omega}+\frac{1}{(\omega^2)^{1023}\times \omega^2}\\=4+2\omega+2\omega^2=2(1+(1+\omega+\omega^2))=2\times 1=\boxed{2}

@Abdur Rehman Zahid i didn't get the a=1,b=1 part can you explain more explicit ?

Stephen Thajeb - 4 years, 7 months ago

Same solution...

Dev Sharma - 5 years, 7 months ago
Chew-Seong Cheong
Oct 24, 2015

x 4 + 3 x 3 + 4 x 2 + 3 x + 1 = 0 Divided throughout by x 2 x 2 + 3 x + 4 + 3 x + 1 x 2 = 0 ( x + 1 x ) 2 + 3 ( x + 1 x ) + 2 = 0 ( x + 1 x + 1 ) ( x + 1 x + 2 ) ( x 2 + 2 x + 1 ) ( x 2 + x + 1 ) = 0 ( x + 1 ) 2 ( x 2 + x + 1 ) = 0 x = { a = 1 b = 1 c = ω d = ω 2 where ω and ω 2 are the complex third roots of unity. \begin{aligned} x^4+3x^3+4x^2+3x+1 & = 0 \quad \quad \small \color{#3D99F6}{\text{Divided throughout by }x^2} \\ x^2+3x+4+\frac{3}{x}+\frac{1}{x^2} & = 0 \\ \left(x+ \frac{1}{x} \right)^2 + 3 \left(x+ \frac{1}{x} \right) + 2 & = 0 \\ \left(x+ \frac{1}{x} + 1\right) \left(x+ \frac{1}{x} + 2 \right) \\ (x^2+2x+1) (x^2+x+1) & = 0 \\ (x+1)^2(x^2+x+1) & = 0 \\ \Rightarrow x & = \begin{cases} a = -1 \\ b = -1 \\ c = \omega \\ d = \omega^2 \quad \quad \small \color{#3D99F6}{\text{where }\omega \text{ and } \omega^2 \text{ are the complex third roots of unity.}} \end{cases} \end{aligned}

Therefore,

a 1024 + b 1024 + c 1024 + d 1024 + 1 a 1024 + 1 b 1024 + 1 c 1024 + 1 d 1024 = ( 1 ) 1024 + ( 1 ) 1024 + ω 1024 + ω 2048 + 1 ( 1 ) 1024 + 1 ( 1 ) 1024 + 1 ω 1024 + 1 ω 2048 Note that ω 3 = 1 = 1 + 1 + ω + ω 2 + 1 + 1 + 1 ω + 1 ω 2 = 1 + 1 + ω + ω 2 + 1 + 1 + ω 2 + ω = 4 + 2 ( ω + ω 2 ) Since ω 2 + ω + 1 = 0 = 4 + 2 ( 1 ) = 2 \displaystyle a^{1024} + b^{1024} + c^{1024} + d^{1024} + \frac{1}{a^{1024}} + \frac{1}{b^{1024}} + \frac{1}{c^{1024}} + \frac{1}{d^{1024}} \\ \displaystyle = (-1)^{1024} + (-1)^{1024} + \omega^{1024} + \omega^{2048} + \frac{1}{(-1)^{1024}} + \frac{1}{(-1)^{1024}} + \frac{1}{\omega^{1024}} + \frac{1}{\omega^{2048}} \quad \quad \small \color{#3D99F6}{\text{Note that } \omega^3 = 1} \\ \displaystyle = 1 + 1 + \omega + \omega^{2} + 1 + 1 + \frac{1}{\omega} + \frac{1}{\omega^{2}} \\ = 1 + 1 + \omega + \omega^{2} + 1 + 1 + \omega^2 + \omega \\ = 4 + 2(\omega + \omega^2) \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \small \color{#3D99F6}{\text{Since } \omega^2 + \omega + 1 = 0} \\ = 4 + 2(-1) = \boxed{2}

Very nice.

Abdur Rehman Zahid - 5 years, 7 months ago
Aareyan Manzoor
Oct 22, 2015

divide by x 2 x^2 and substitute y = x + 1 x y=x+\dfrac{1}{x} . solve for y and you get -1 or-2. note that x 2 + 1 x 2 = y 2 2 x^2+\dfrac{1}{x^2}=y^2-2 and like this we can find all power of. we can see the recurence that no matter how greater the power of 2≠0, it will always be -1 or 2. so two roots give -1, other 2 give 2. the sum becomes 2*2+2(-1)=2

Hung Woei Neoh
Apr 13, 2016

For those who do not know the complex cube roots of unity (like me), you can solve this with Newton's sums.

x 4 + 3 x 3 + 4 x 2 + 3 x + 1 = 0 x^4 + 3x^3 + 4x^2 + 3x + 1 = 0

Notice that 1 3 + 4 3 + 1 = 0 1 - 3 + 4 - 3 + 1 = 0

From this, we can know that x = 1 x = -1 is a root of the equation.

Factorize x + 1 x + 1 out and you get:

( x + 1 ) ( x 3 + 2 x 2 + 2 x + 1 ) = 0 (x + 1)(x^3 + 2x^2 + 2x + 1) = 0

Now, notice again that 1 + 2 2 + 1 = 0 - 1 + 2 - 2 + 1 = 0

From this, we know that the root x = 1 x = -1 is repeated

Factorize it out again, and you have:

( x + 1 ) 2 ( x 2 + x + 1 ) = 0 (x + 1)^2 (x^2 + x + 1) = 0

The discriminant for ( x 2 + x + 1 ) = 1 2 4 ( 1 ) ( 1 ) = 3 (x^2 + x + 1) = 1^2 - 4(1)(1) = -3

The last 2 2 solutions for the equation are complex roots.

But first, substitute the 2 known roots ( c = d = 1 ) (c = d = -1) into the expression:

a 1024 + b 1024 + c 1024 + d 1024 + 1 a 1024 + 1 b 1024 + 1 c 1024 + 1 d 1024 a^{1024} + b^{1024} + c^{1024} + d^{1024} + \dfrac{1}{a^{1024}} + \dfrac{1}{b^{1024}} + \dfrac{1}{c^{1024}} + \dfrac{1}{d^{1024}}

= a 1024 + b 1024 + ( 1 ) 1024 + ( 1 ) 1024 + 1 a 1024 + 1 b 1024 + 1 ( 1 ) 1024 + 1 ( 1 ) 1024 = a^{1024} + b^{1024} + (-1)^{1024} + (-1)^{1024} + \dfrac{1}{a^{1024}} + \dfrac{1}{b^{1024}} + \dfrac{1}{(-1)^{1024}} + \dfrac{1}{(-1)^{1024}}

= a 1024 + b 1024 + 1 a 1024 + 1 b 1024 + 4 = a^{1024} + b^{1024} + \dfrac{1}{a^{1024}} + \dfrac{1}{b^{1024}} + 4

= a 1024 + b 1024 + a 1024 + b 1024 a 1024 b 1024 + 4 = a^{1024} + b^{1024} + \dfrac{a^{1024} + b^{1024}}{a^{1024}b^{1024}} + 4

= a 1024 + b 1024 + a 1024 + b 1024 ( a b ) 1024 + 4 = a^{1024} + b^{1024} + \dfrac{a^{1024} + b^{1024}}{(ab)^{1024}} + 4

Now, let a a and b b be the roots of ( x 2 + x + 1 ) (x^2 + x + 1) . From Vieta's formula, we get:

a + b = 1 a + b = -1

a b = 1 ab = 1

( a b ) 1024 = 1 \implies(ab)^{1024} = 1

Substitute this into the expression, and we have:

a 1024 + b 1024 + a 1024 + b 1024 ( a b ) 1024 + 4 a^{1024} + b^{1024} + \dfrac{a^{1024} + b^{1024}}{(ab)^{1024}} + 4

= a 1024 + b 1024 + a 1024 + b 1024 + 4 = a^{1024} + b^{1024} + a^{1024} + b^{1024} + 4

= 2 ( a 1024 + b 1024 ) + 4 = 2(a^{1024} + b^{1024}) + 4

This is where Newton's sums comes in.

a + b = 1 a + b = -1

a 2 + b 2 = ( a + b ) 2 2 a b = ( 1 ) 2 2 ( 1 ) = 1 a^2 + b^2 = (a + b)^2 - 2ab = (-1)^2 - 2(1) = -1

a 3 + b 3 = ( a + b ) ( a 2 + b 2 ) a b ( a + b ) = 1 ( 1 ) 1 ( 1 ) = 2 a^3 + b^3 = (a + b)(a^2 + b^2) - ab(a + b) = -1(-1) - 1(-1) = 2

a 4 + b 4 = ( a + b ) ( a 3 + b 3 ) a b ( a 2 + b 2 ) = 1 ( 2 ) 1 ( 1 ) = 1 a^4 + b^4 = (a + b)(a^3 + b^3) - ab(a^2 + b^2) = -1(2) - 1(-1) = -1

a 5 + b 5 = ( a + b ) ( a 4 + b 4 ) a b ( a 3 + b 3 ) = 1 ( 1 ) 1 ( 2 ) = 1 a^5 + b^5 = (a + b)(a^4 + b^4) - ab(a^3 + b^3) = -1(-1) - 1(2) = -1

a 6 + b 6 = ( a + b ) ( a 5 + b 5 ) a b ( a 4 + b 4 ) = 1 ( 1 ) 1 ( 1 ) = 2 a^6 + b^6 = (a + b)(a^5 + b^5) - ab(a^4 + b^4) = -1(-1) - 1(-1) = 2

a 7 + b 7 = ( a + b ) ( a 6 + b 6 ) a b ( a 5 + b 5 ) = 1 ( 2 ) 1 ( 1 ) = 1 a^7 + b^7 = (a + b)(a^6 + b^6) - ab(a^5 + b^5) = -1(2) - 1(-1) = -1

a 8 + b 8 = ( a + b ) ( a 7 + b 7 ) a b ( a 6 + b 6 ) = 1 ( 1 ) 1 ( 2 ) = 1 a^8 + b^8 = (a + b)(a^7 + b^7) - ab(a^6 + b^6) = -1(-1) - 1(2) = -1

a 9 + b 9 = ( a + b ) ( a 8 + b 8 ) a b ( a 7 + b 7 ) = 1 ( 1 ) 1 ( 1 ) = 2 a^9 + b^9 = (a + b)(a^8 + b^8) - ab(a^7 + b^7) = -1(-1) - 1(-1) = 2

and the list goes on......

From this list, you can notice that the Newton's sums will have a repeating sequence of 1 , 1 , 2 -1, -1, 2 . Don't believe? Try expanding further and you'll see the pattern holds true. Thus, we can conclude that

a n + b n = { 1 n 1 or n 2 ( mod 3 ) 2 n 0 ( mod 3 ) a^n + b^n = \begin{cases} -1 & \quad n \equiv 1 \;\text{or}\;n \equiv 2 \quad(\text{mod} \quad3)\\ 2 & \quad n \equiv 0 \quad(\text{mod} \quad3) \end{cases}

With this general expression, we can know the value of ( a 1024 + b 1024 ) (a^{1024} + b^{1024}) by determining the remainder of 1024 1024 when divided by 3 3 :

n = 1024 = 341 1 3 1 ( mod 3 ) n = 1024 = 341\dfrac{1}{3} \equiv 1 \quad(\text{mod}\quad3)

Therefore,

a 1024 + b 1024 = 1 a^{1024} + b^{1024} = -1

The final value of the expression is:

2 ( a 1024 + b 1024 ) + 4 2(a^{1024} + b^{1024}) + 4

= 2 ( 1 ) + 4 = 2 =2(-1) + 4 = \boxed{2}

Marvin Chong
Feb 8, 2020

Let the equation be f ( x ) f(x) .

First use the Rational Root Theorem see that the possible roots are ± 1 \pm{1} . Plug them both in to see if they work. After calculations, it should be clear that f ( 1 ) = 0 f(-1) = 0 whilst f ( 1 ) > 0 f(1) > 0 .

Note that when x 4 × f ( 1 x ) = 0 f ( 1 x ) = 0 x^{4} \times f(\frac{1}{x}) = 0 \Rightarrow f(\frac{1}{x}) = 0 . Therefore, if f ( x ) = 0 f(x) = 0 , f ( 1 x ) = 0 f(\frac{1}{x}) = 0 . This works because the value of the coefficients are symmetrical.

Since x = 1 x = -1 is a factor of f ( x ) f(x) , 1 x \frac{1}{x} = 1 1 = 1 \frac{1}{-1} = -1 is also a factor of f ( x ) f(x) .

After using long division to calculate f ( x ) ( x 1 ) 2 \frac{f(x)}{(x-1)^{2}} ,

f ( x ) = ( x 1 ) 2 ( x 2 + x + 1 ) f(x) = (x-1)^{2}(x^{2}+x+1)

We can use the Quadratic Formula to calculate the roots of ( x 2 + x + 1 ) (x^{2}+x+1) .

x = 1 ± 1 4 2 = 1 ± 3 i 2 x = \frac{-1\pm\sqrt{1-4}}{2} = \frac{-1\pm\sqrt{3}i}{2}

Now that the roots are found, we can plug them into the expression. x = 1 x = -1 is fairly straight forward. x = 1 ± 3 i 2 x = \frac{-1\pm\sqrt{3}i}{2} can be a bit of a pain if simply just plugged in and expanded.

Let c = ( 1 + 3 i 2 ) 1024 c = (\frac{-1+\sqrt{3}i}{2})^{1024} and d = ( 1 3 i 2 ) 1024 d = (\frac{-1-\sqrt{3}i}{2})^{1024} , (In retrospect, I just realized I overrode the value of c c and d d ... oh well.)

If we apply the Perfect square Identity to both of these equations, the value inside the bracket alternates between these two values (as according to the laws behind complex numbers): 1 + 3 i 2 \frac{-1+\sqrt{3}i}{2} and 1 3 i 2 \frac{-1-\sqrt{3}i}{2} .

For c c , let the exponent follow the formula of 2 n 2^{n} , when n n is an even number (2 because the exponent halves after you apply the perfect square identity), it will be 1 + 3 i 2 \frac{-1+\sqrt{3}i}{2} , and if it is odd, it will be 1 3 i 2 \frac{-1-\sqrt{3}i}{2} . As for d d , it is the same, but since it begins with a different parity, it will be the inverse of the case of c c .

Since the exponent value that we want (which is one) is simply just 2 0 2^{0} , which is the same parity as the starting value, the value inside the bracket stays the same. Thus,

c = 1 + 3 i 2 c = \frac{-1+\sqrt{3}i}{2} and d = 1 3 i 2 d = \frac{-1-\sqrt{3}i}{2} ,

We can move on to substituting these values, but by first simplifying the process.

c + d + 1 c + 1 d c + d + \frac{1}{c} + \frac{1}{d}

= c 2 d + c d 2 + ( c + d ) c d = \frac{c^{2}d+cd^{2}+(c+d)}{cd}

= c d ( c + d ) + ( c + d ) c d = \frac{cd(c+d)+(c+d)}{cd}

= ( c + d ) ( c d + 1 ) c d = \frac{(c+d)(cd+1)}{cd}

c + d = 1 c + d = -1 and c d = 2 cd = 2

Substituting them into ( c + d ) ( c d + 1 ) c d \frac{(c+d)(cd+1)}{cd} will give us 2 \boxed{-2} .

Therefore, we can plug these values into the expression, which will be 1 + 1 + 1 + 1 2 = 2 1 + 1 + 1 + 1 - 2 = \boxed{2} .

Shubham Gupta
Dec 10, 2015

Roots can be found out by dividing with x^2 and substituting in eqn. Then its done and answer is 2

Take common (x+1) by splitting 3x^3 as 2+1 next coeff as 2+2 next as 2+1. Then from x^3+2x^2+x+1 take x^3+1 and2x^2+2x as groups. We can get x+1 as common again. Hence roots come as -1,-1,w,w^2. Thus its solved.

Aakash Khandelwal
Oct 22, 2015

Roots are(-1,-1,w,w^2)

The last term should be 1/d^1024 in order to get symmetry

Aakash Khandelwal - 5 years, 7 months ago

Log in to reply

Now its correct

Aakash Khandelwal - 5 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...